2019
DOI: 10.3389/fpls.2019.00469
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting the Genetic Basis of Grain Size and Weight in Barley (Hordeum vulgare L.) by QTL and Comparative Genetic Analyses

Abstract: Grain size and weight are crucial components of barley yield and quality and are the target characteristics of domestication and modern breeding. Despite this, little is known about the genetic and molecular mechanisms of grain size and weight in barley. Here, we evaluated nine traits determining grain size and weight, including thousand grain weight (Tgw), grain length (Gl), grain width (Gw), grain length-width ratio (Lwr), grain area (Ga), grain perimeter (Gp), grain diameter (Gd), grain roundness (Gr), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
47
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 102 publications
(143 reference statements)
7
47
1
Order By: Relevance
“…Identification and mapping QTL for grain size-related characteristics have been achieved in various genetic backgrounds (Walker et al 2013;Watt et al 2019;Xu et al 2018a;Zhou et al 2016). In many instances, the identified QTL share close homology to grain size-related genes identified in wheat and rice resulting in promising putative candidates for further research, although research of homologous gene regions in barley is restricted to a small number of publications (Bélanger et al 2014;Wang et al 2019;Watt et al 2019;Xu et al 2018a). Despite our current understanding of QTL regions contributing to grain size, only one study has fine mapped a major QTL and identified a potential candidate gene (Watt et al 2019).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Identification and mapping QTL for grain size-related characteristics have been achieved in various genetic backgrounds (Walker et al 2013;Watt et al 2019;Xu et al 2018a;Zhou et al 2016). In many instances, the identified QTL share close homology to grain size-related genes identified in wheat and rice resulting in promising putative candidates for further research, although research of homologous gene regions in barley is restricted to a small number of publications (Bélanger et al 2014;Wang et al 2019;Watt et al 2019;Xu et al 2018a). Despite our current understanding of QTL regions contributing to grain size, only one study has fine mapped a major QTL and identified a potential candidate gene (Watt et al 2019).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…The eight 9K iSelect markers defining this QTL can be positioned on the current physical map at 482-500MB on 7H, corresponding to the location of HvAT10. Wang et al 28 also identified a QTL for grain length:width, grain perimeter, and grain roundness at the same location.…”
mentioning
confidence: 96%
“…In rice, maize, wheat, and barley thousands of quantitative trait loci (QTL) influencing grain size have collectively been detected, yet only a small fraction of underlying candidate genes have been functionally annotated using advanced molecular approaches such as gene cloning with the majority of studies in rice ( Ayoub et al., 2002 ; Huang et al., 2013 ; Walker et al., 2013 ; Chen et al., 2016 ; Yu et al., 2017 ; Azizi et al., 2019 ; Li et al., 2019 ; Wang Q. et al., 2019 ; Watt et al., 2019 ). Broadly, the regulatory pathways involved in grain size regulation are represented by: hormone signaling, IKU pathway, G-protein signaling, ubiquitin–proteasome pathway, the mitogen-activated protein kinase pathway and transcription factors ( Li and Li, 2016 ; Azizi et al., 2019 ).…”
Section: Genetic Control Of Grain Sizementioning
confidence: 99%